Animal models in cardiovascular research - Gross, David R. (Developments in Cardiovascular Medicine, 1994)
Interest in the humane and scientifically justifiable use of research animals has intensified since the publication of the first edition of this textbook. This completely revised and updated text provides information essential to any researcher interested in using animal models for cardiovascular research, or any research which requires normal cardiovascular function. The format and presentation have been changed to make the text more easy to read and use. An introductory chapter offers general principles of animal selection, pre and post-operative care, preanesthesia, chemical restraint, analgesia, and the recognition of pain. The number of references cited has been almost doubled over the previous text and the chapter tabulating normal cardiovascular parameters from intact, awake animals, of those species commonly used in research, has been greatly expanded. Other chapters providing comprehensive data on the cardiovascular effects of opioids, tranquilizers, anesthetic agents and other drugs commonly used in cardiovascular research have been expanded with special emphasis on species variability to drug effects. The chapters on both naturally occurring and iatrogenic models of cardiovascular disease have also been expanded and updated